Problems That Arise in a Multicultural Environment: African and Western Cultures - Flis, Joanna (Roczniki Kulturoznawcze, 2023)
The essay presents observations of a student regarding cultural differences in Polish university environment. The author notes differences in various fields of functioning of her group: concerning the rules within the university and outside of it - in the area of everyday life. They are focused especially on those elements that - although obvious - do not always serve to shape open attitudes towards other people.